Floristic composition of Palpa district, west Nepal - Mahato, Ras Bihari (Nepalese Journal of Biosciences, 2014)
The present study documents the floristic composition of the vascular plants (Pteridophytes, Gymnosperms, and Angiosperms) of Palpa district, West Nepal. A total of 467 species plants belonging to 163 families, 357 genera were recorded from the study area. Among them Pteridophytes are comprised of 37 species, Gymnosperms 2 species and Angiosperms 428 species (Dicotyledones 336 and Monocotyledones 92 species). Floristic analysis showed that Dicotyledones comprise (71.9%), Monocotyledones (19.7%), Gymnosperms (0.4%) and Pteridophytes (8.00%). Although total plant species were distributed among 163 families and 357 genera, 52.25% of the species belonged to only ten families. Out of 467 species Hardwickia binata Roxb. is reported as new addition to the flora of Nepal. Five species of threatened plants were recorded from the study area. These are Acacia catechu-threatened (T), Aegle marmelos-(T), Dioscorea deltoidea-(T), Elaeocarpus sphaericus-vulnerable (V) and Rauvolfia serpentina-endangered (E).